AN ANALYSIS AND TRANSLATION INTO FILIPINO OF IBANAG PROVERBS - Matammu, Corazon (International Journal of Arts, Sciences and Education, 2022)
The purpose of this study is to identify the proverbs of an ethnolinguistic group, the Ibanag to be analyzed and translated into Filipino. Qualitative descriptive analysis was used in the study. Data were collected in several barangays of Tuguegarao city that speak the Ibanag language. By translating the Ibanag proverbs into Filipino, the lessons contained in them became clear and understood. The study proved that the proverbs reflect various topics related to the way of life and customs of the indigenous Ibanag in Cagayan particularly in the city of Tuguegarao. A fact that describes and characterizes their instinct. And also proof that to this day these proverbs are heard and still used especially in giving advice to young people and are still part of their daily lives.